Diagnosis and Management of Primary Effusion Lymphoma in the Immunocompetent and Immunocompromised Hosts - Ammari, Zaid A.; Mollberg, Nathan M.; Abdelhady, Khaled; Mansueto, Mario D.; Massad, Malek G. (The Thoracic and Cardiovascular Surgeon, 2013)
Primary effusion lymphoma (PEL) is an uncommon non-Hodgkin lymphoma associated with human herpes virus-8 (HHV-8) that grows mainly in serous body cavities. The most common presentation of PEL is that of a young immunocompromised male with shortness of breath, as the pleural cavity is most commonly affected. Diagnosis is primarily based on fluid cytology in which PEL cells display variable morphology and a null lymphocyte immunophenotype; however, evidence of HHV-8 infection within the neoplastic cell is essential. Patients have commonly been treated with systemic multidrug chemotherapy and antiretroviral therapy if they were HIV positive or were immunocompromised for other reasons. In the immunocompetent patient, there have been no agreed-upon pathways for management of this condition. Progression of disease is common and median survival is approximately 6 months. Novel intrapleural treatments with antiviral agents such as intracavity cidofovir have shown to be effective in controlling local disease, and ongoing clinical trials may provide some promise in the treatment for this condition.
Keywords: primary effusion lymphoma; immunocompromised; immunocompetent; HHV-8; chemotherapy